Cirebon Dialect Variation in Indonesian Conversations of Faculty of Education and Science, Universitas Swadaya Gunung Jati Students - Sabilla, Elisa Sal; Nadzifah, Naurah Dhiya; Muanisah, Putri May; Gloriani, Yusida; Romansyah, Khalimi (Green Publisher Indonesia, 2024)
This research discusses the variations of Cirebon dialect in Indonesian conversations among students at the Faculty of Education and Science, Swadaya Gunung Jati University, Cirebon. The research background is based on initial findings in student conversations, which show the diversity of dialects when communicating in Indonesian. UGJ students come from various regions, influencing their communication styles, thus resulting in diverse variations of Indonesian used as a means of communication among students, including dialectal variants. This study examines dialectal variations based on phonological and lexical aspects. The method used is qualitative descriptive with conversation monitoring techniques among students. The research findings indicate the presence of Cirebon dialect variations in Indonesian conversations among FPS UGJ Cirebon students. Dialectal variations include: Indramayu dialect, Javanese-Sundanese dialect, Arjawinangun dialect, Plered dialect, and Gegesik dialect. Phonological and lexical analysis highlight differences in word pronunciation, intonation, as well as the use of particles, pronouns, nouns, and adjectives.